Metal artifact reduction in CT using fusion based prior image. Issue 8 (3rd July 2013) - Wang, Jun; Wang, Shijie; Chen, Yang; Wu, Jiasong; Coatrieux, Jean‐Louis; Luo, Limin
Abstract : Purpose: : In computed tomography, metallic objects in the scanning field create the so‐called metal artifacts in the reconstructed images. Interpolation‐based methods for metal artifact reduction (MAR) replace the metal‐corrupted projection data with surrogate data obtained from interpolation using the surrounding uncorrupted sinogram information. Prior‐based MAR methods further improve interpolation‐based methods by better estimating the surrogate data using forward projections from a prior image. However, the prior images in most existing prior‐based methods are obtained from segmented images and misclassification in segmentation often leads to residual artifacts and tissue structure loss in the final corrected images. To overcome these drawbacks, the authors propose a fusion scheme, named fusion prior‐based MAR (FP‐MAR). Methods: : The FP‐MAR method consists of (i) precorrect the image by means of an interpolation‐based MAR method and an edge‐preserving blur filter; (ii) generate a prior image from the fusion of this precorrected image and the originally reconstructed image with metal parts removed; (iii) forward project this prior image to guide the estimation of the surrogate data using well‐developed replacement techniques. Results: : Both simulations and clinical image tests are carried out to show that the proposed FP‐MAR method can effectively reduce metal artifacts. A comparison with other MAR methods demonstrates that the FP‐MAR method performs better in artifact suppression and tissue feature preservation. Conclusions: : From a wide range of clinical cases to which FP‐MAR has been tested (single or multiple pieces of metal, various shapes, and sizes), it can be concluded that the proposed fusion based prior image preserves more tissue information than other segmentation‐based prior approaches and can provide better estimates of the surrogate data in prior‐based MAR methods.